An evaluation of the BrainLAB 6D ExacTrac/Novalis Tx System for image-guided intracranial radiotherapy. - Montgomery, Claire; Collins, Mark (Journal of Radiotherapy in Practice, 2017)
PurposeStereotactic-fractionated radiotherapy and radiosurgery (RS) for benign and malignant intracranial lesions relies on a very high degree of accuracy in dose alignment due to the ablative dose delivered, and therefore requires a high-precision image guidance modality. The aim of this review is to investigate the localisation and verification accuracy performance of ExacTrac (ET) and Novalis Tx System.Materials and methodsA systematic review of the database Science Direct was carried out using search terms ‘stereotactic radiotherapy (SRT)’ and ‘ET’. All articles before 2000 were excluded. Only articles that involved intracranial lesions, with the exception of one article, were included in the final review.ResultsResults from gold standard Hidden Target Tests and patient data show that patient position can be reproduced within 1·0 mm with the use of ET imaging. In addition, the 6 degrees of freedom algorithm function of ET allows for better translational accuracy as well optimal positioning when rotations are corrected for. Studies showed excellent correlation (p<0·01) between bony ET images and cone beam computed tomography (CBCT) soft tissue registration, evidencing the safe reliance of bony anatomy for image guidance via ET. Shifts were found to be comparable between CBCT and ET.ConclusionThere is the need for regular calibration to prevent systematic errors and potential geographic miss. However, due to ET’s additional benefits, including reduced concomitant dose and faster imaging time, ET is the superior image guidance modality for RS/SRT in the treatment of intracranial lesions.